Human Acts by Han Kang as a Narrative of Trauma and Human Rights - Dahal, Tara Kumar (International Journal of Humanities, Education, and Social Sciences, 2025)
This paper examines Han Kang’s novel Human Acts as a trauma and human rights narrative, with a focus on the 1980 Gwangju Uprising in South Korea. The novel recounts the suppression of a student uprising in Gwangju, depicting the experiences of the boy at the center of the story and those of his acquaintances. The research examines the personal, parochial, and political dimensions of trauma in the narrative, addressing the complex interplay between individual experiences and public history. The study highlights the significance of Kang's work, particularly in light of South Korea's recent history, including the 2014 ferry disaster and the 2017 killings by city authorities, which echo the traumas of the Gwangju Massacre. The narrative's vivid depiction of violence and suffering emphasizes the importance of understanding these events to foster awareness and connection to collective trauma. The research uses literary trauma theory and human rights theory to analyze the novel, examining how Kang's narrative portrays the individual and collective trauma of the 1980 Military Coup. It examines the narrative structure, character development, and thematic elements of the novel, with a focus on the representation of violence, resistance, memory, and human rights. The findings suggest that Human Acts effectively convey the multifaceted nature of trauma and its enduring impact on individuals and society. The novel serves as a crucial narrative that contributes to the discourse on trauma, memory, and human rights, highlighting the importance of acknowledging past atrocities and striving for justice and accountability.